2013
DOI: 10.1111/tpj.12324
|View full text |Cite
|
Sign up to set email alerts
|

Amyloplast displacement is necessary for gravisensing in Arabidopsis shoots as revealed by a centrifuge microscope

Abstract: SUMMARYThe starch-statolith hypothesis proposes that starch-filled amyloplasts act as statoliths in plant gravisensing, moving in response to the gravity vector and signaling its direction. However, recent studies suggest that amyloplasts show continuous, complex movements in Arabidopsis shoots, contradicting the idea of a so-called 'static' or 'settled' statolith. Here, we show that amyloplast movement underlies shoot gravisensing by using a custom-designed centrifuge microscope in combination with analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 34 publications
4
51
0
Order By: Relevance
“…Y values were measured to indicate vertical displacement of plastids. Y was the distance in micrometers of the position of the center of brightness of a plastid from its original position at any given time point (Toyota et al, 2013). Measurements were performed using one or two S2 cells from at least three individuals of each genotype.…”
Section: Analysis Of Amyloplast Sedimentationmentioning
confidence: 99%
“…Y values were measured to indicate vertical displacement of plastids. Y was the distance in micrometers of the position of the center of brightness of a plastid from its original position at any given time point (Toyota et al, 2013). Measurements were performed using one or two S2 cells from at least three individuals of each genotype.…”
Section: Analysis Of Amyloplast Sedimentationmentioning
confidence: 99%
“…Abnormal amyloplast sedimentation in graviperceptive endodermal cells and dramatic reduction in the gravitropism of inflorescence stems, hypocotyls, and petioles were observed in shoot gravitropism (sgr) 2 plants Mano et al 2006;Morita et al 2002;Toyota et al 2013b). The protein sequence of SGR2 is homologous to PA-hydrolyzing phospholipase А 1 .…”
Section: Phospholipase Amentioning
confidence: 98%
“…The so-called Bmodel of hydrostatic pressure^was proposed to explain several observations. Starchless mutants have some residual gravitropism, and starchdeficient mutants have a normal graviresponse to hypergravity (Toyota et al 2013b;Wolverton et al 2011). Cells in the root distal elongation zone of higher plants and characean algae internodal cells contain no sedimentable amyloplasts, and lateral root gravitropism is initiated before their amyloplasts emerge.…”
Section: Models Of Gravity Perceptionmentioning
confidence: 99%
“…One example is to validate the statolith hypothesis of plant gravisensing from the viewpoint of microrheological feature of amyloplast movement in the plant root gravity-sensing cells. While it is well known that the sedimentation movement of amyloplasts primarily triggers the asymmetric distribution of auxin and then leads to the differential growth of the plant root (Vanneste and Friml 2009;Leitz et al 2009;Morita 2010;Sato et al 2015), the inhomogeneous structures in statocytes are also found to significantly affect the movements of amyloplasts and the resulted gravimorphogenesis (Weise et al 2000;Toyota et al 2013a). Microrheological analysis, frequently used to detect micro-mechanical properties of cytoskeletal network, is employed for the first time and indicates that the intracellular environment of columella cells exhibits the spatial heterogeneity and the cage-confinement on amyloplasts.…”
Section: Biomechanical and Mechanobiological Approachesmentioning
confidence: 99%